Comparative perspectives on the role of the trustees and the managing agent as dramatis personae in the governance of sectional title schemes in South Africa - Durham, Carryn Melissa (Stellenbosch : Stellenbosch University, 2016)
Thesis (LLD)--Stellenbosch University, 2016